Globalisation and the multi-dimensional crisis. The inclusive democracy approach - Fotopoulos, Takis (Universidad Nacional de Quilmes, 2001)
The aim of this paper is to examine, through a discussion of the main theoretical approaches to globalisation, the various aspects of the present multidimensional crisis (economic, political, social, cultural and ecological) in order to draw some conclusions on the conditions under which a way out of the crisis can be found. The thesis supported by this article is that the ultimate cause of this crisis is the huge and growing concentration of power that the present institutional framework of the internationalised market economy creates. ?his implies that a way out of it can only be found through a process of creating a democratic and sustainable globalisation based on a new democratic world order. Democratic, in the sense that it is founded on a comprehensive political, economic and ecological democracy, what I call an inclusive democracy, and sustainable, in the sense that it re-integrates society with nature.